2008
DOI: 10.1128/jvi.01992-07
|View full text |Cite
|
Sign up to set email alerts
|

Melon Chlorotic Leaf Curl Virus : Characterization and Differential Reassortment with Closest Relatives Reveal Adaptive Virulence in the Squash Leaf Curl Virus Clade and Host Shifting by the Host-Restricted Bean Calico Mosaic Virus

Abstract: The genome components of the Melon chlorotic leaf curl virus (MCLCuV) were cloned from symptomatic cantaloupe leaves collected in Guatemala during 2002. The MCLCuV DNA-A and DNA-B components shared their closest nucleotide identities among begomoviruses, at ϳ90 and 81%, respectively, with a papaya isolate of MCLCuV from Costa Rica. The closest relatives at the species level were other members of the Squash leaf curl virus (SLCV) clade, which is endemic in the southwestern United States and Mexico. Biolistic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 45 publications
0
26
1
Order By: Relevance
“…Bean calico mosaic virus (BCaMV) is a bean‐restricted virus and does not infect cucurbits in laboratory conditions. Interestingly, interaction of either DNA‐A or DNA‐B components of BCaMV with MCLCuV resulted in infection to many cucurbit species [27].…”
Section: Genetic Effects On “Geminivirus” Evolutionmentioning
confidence: 99%
“…Bean calico mosaic virus (BCaMV) is a bean‐restricted virus and does not infect cucurbits in laboratory conditions. Interestingly, interaction of either DNA‐A or DNA‐B components of BCaMV with MCLCuV resulted in infection to many cucurbit species [27].…”
Section: Genetic Effects On “Geminivirus” Evolutionmentioning
confidence: 99%
“…Degenerate primers are also widely used for PCR amplification to distinguish the identity of the virus from other begomoviruses [3,5,6,12,14]. Idris et al [15] described the detection of CuLCrV and other begomoviruses with RFLP following PCR amplification using degenerate primers and digestion with restriction enzymes AccI, SalI, or SpeI to confirm the identity of the viral DNA-A. In another study, Turechek et al [16] used nucleic acid hybridization after blotting the cross-sections of symptomatic watermelon plants onto a nitrocellulose membrane to detect CuLCrV.…”
Section: Introductionmentioning
confidence: 99%
“…ORFs on DNA-A and DNA-B of this isolate were organized in a similar fashion to other already characterized begomovirus namely [34]. Recently it has been demonstrated that bean Bean calico mosaic virus (BCaMV) was differentially assisted in systemically infecting the cucurbit test species by the components of the four cucurbit-adapted begomoviruses, which resulted in shift of the host by BCaMV [35].…”
Section: Discussionmentioning
confidence: 95%